Preserving built heritage through education & research for sustainability: IIUM perspective & experiences - Mohd Nawawi, Norwina; Salleh, Nurul Hamiruddin; Sapian, Abdul Razak (2019)
The presentation put together efforts by IIUM as a university, as an educational centre, in instilling appreciation and awareness of history and heritage through teaching and learning, research and consultancy. The intention of the quest is not only to study or appreciate the physical structures per se but as lessons learnt on the civilisation of the past, as mentioned in the pages of the Holy Quran for a better world. The presentation put through courses of the Kulliyyah of Architecture and Environmental Design (KAED) and highlights Heritage Studies course for Architecture. The works of Islamic Architectural Heritage research unit (ISARCH); TRGS on studies of Malay Settlement via the use of BIM; and consultancy works that applied theory to practice, were also revealed through the documentation in the form of research papers, exhibition posters and books. IIUM acknowledged that only through knowledge can heritage be valued and be preserved for posterity in many guises and forms in time.